The ubiquitin-dependent ATPase p97 removes cytotoxic trapped PARP1 from chromatin - Krastev, Dragomir B.; Li, Shudong; Sun, Yilun; Wicks, Andrew J.; Hoslett, Gwendoline; Weekes, Daniel; Badder, Luned M.; Knight, Eleanor G.; Marlow, Rebecca; Pardo, Mercedes Calvo; Yu, Lu; Talele, Tanaji T.; et al. (Nature cell biology, 2022)
Poly (ADP-ribose) polymerase (PARP) inhibitors elicit antitumour activity in homologous recombination-defective cancers by trapping PARP1 in a chromatin-bound state. How cells process trapped PARP1 remains unclear. Using wild-type and a trapping-deficient PARP1 mutant combined with rapid immunoprecipitation mass spectrometry of endogenous proteins and Apex2 proximity labelling, we delineated mass spectrometry-based interactomes of trapped and non-trapped PARP1. These analyses identified an interaction between trapped PARP1 and the ubiquitin-regulated p97 ATPase/segregase. We found that following trapping, PARP1 is SUMOylated by PIAS4 and subsequently ubiquitylated by the SUMO-targeted E3 ubiquitin ligase RNF4, events that promote recruitment of p97 and removal of trapped PARP1 from chromatin. Small-molecule p97-complex inhibitors, including a metabolite of the clinically used drug disulfiram (CuET), prolonged PARP1 trapping and enhanced PARP inhibitor-induced cytotoxicity in homologous recombination-defective tumour cells and patient-derived tumour organoids. Together, these results suggest that p97 ATPase plays a key role in the processing of trapped PARP1 and the response of tumour cells to PARP inhibitors. Krastev et al. report that trapped PARP1 undergoes SUMOylation, followed by ubiquitylation, resulting in the recruitment of the p97 ATPase to remove trapped PARP1 from chromatin and prevent PARP inhibitor-induced cytotoxicity.